The Effectiveness of Microplastic Removal in a Lake on the University of Indonesia Campus Using PVC (Polyvinyl Chloride) Ultrafiltration Membranes - Abrar Rabhani Waluyaning Jati (Pelopor Publikasi Akademika, 2026)
Microplastic pollution is becoming an increasingly important environmental issue due to its potential to degrade water quality and negatively impact ecosystems and human health. Kenanga Lake, located in the University of Indonesia, is a water resource with the potential to be utilized as a raw water source, necessitating pollution control efforts, including those for microplastics. This study aims to design and analyze the performance of a Polyvinyl Chloride (PVC) ultrafiltration system in removing microplastics and improving lake water quality. The research method used a quantitative experimental approach with a pretest–posttest design through testing water samples before and after the filtration process. The PVC ultrafiltration system was equipped with a pretreatment unit in the form of a sediment filter and operated at pressure variations of 1; 1.5; and 2 bar and filtration times of 10, 30, and 60 minutes. The parameters analyzed included the number and characteristics of microplastics, Total Dissolved Solids (TDS), Total Suspended Solids (TSS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Conductivity. System performance was evaluated based on removal efficiency and log removal values. The research results are expected to provide information on the effectiveness of PVC ultrafiltration membranes in reducing microplastics and improving lake water quality as an alternative efficient and sustainable water treatment technology.